A Molecular Imprinted Voltammetric Sensor Based on Carbon Nitride Nanotubes: Application to Determination of Melamine. Issue 13 (16th September 2016) - Yola, Mehmet Lütfi; Eren, Tanju; Atar, Necip
Abstract : Melamine (MEL) has high nitrogen rich content. Because of this situation, it has been illegally added to dairy products by producers to obtain a higher readout of apparent protein content. This has been a cause of serious diseases and many infants have been intoxicated because the addition of MEL into food products can cause death. In this report, a novel molecular imprinted voltammetric sensor based on carbon nitride nanotubes (C3 N4 NTs) modified glassy carbon electrode (GCE) was presented for determination of MEL. The developed surfaces were characterized using scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS). MEL imprinted GCE was prepared via electropolymerization process of 100 mM phenol as monomer in the presence of phosphate buffer solution (PBS) (pH 7.0) containing 25 nM MEL. The linearity range and the detection limit of the method were calculated as 1.0 × 10 −10 – 5.0 × 10 −9 M and 1.0 × 10 −11 M, respectively. The voltammetric sensor was applied to milk samples with good selectivity and recovery. The stability and reproducibility of the voltammetric sensor were also reported.